Rasch Analysis to Evaluate the Psychometric Properties of Junior Metacognitive Awareness Inventory in the Indonesian Context - Sukarelawan, M. I.; Jumadi, J.; Kuswanto, H.; Soeharto, S.; Hikmah, F. N. (Jurnal Pendidikan IPA Indonesia, 2021)
Empirically, metacognitive awareness is one of the main contributors to students' academic success. At the beginning of its development, the Jr.MAI self-report questionnaire was intended to measure students' metacognitive awareness in the United States. However, the evaluation of the psychometric properties for Indonesian high school students is still limited. The original Jr.MAI cannot be applied in Indonesia. By evaluating students' metacognitive awareness using Jr.MAI, teachers can understand students' information and knowledge related to their learning strategies and behaviors. Therefore, this study aims to evaluate the psychometric properties of the Indonesian translation of the Junior Metacognitive Awareness Inventory (Jr.MAI) self-report questionnaire. The Jr.MAI questionnaire consists of 18 items and uses a 5-point Likert scale response. 296 students (Male = 45.9%; Female = 54.1%) of public senior high schools in Indonesia completed the Jr.MAI questionnaire. The Rasch model was used to evaluate the psychometric properties of Jr.MAI. The results showed that the 5-point rating scale with 18 items functioned properly with a good fit, no gender bias, and achieved unidimensionality and local independence assumptions. It proved that the Jr. MAI questionnaire defined the latent variables and classified persons and items properly. Therefore, we concluded that the developed Jr.MAI questionnaire had good psychometric properties to be used by teachers and counselors for measuring and mapping the metacognitive characteristics at the senior high school level.